Publications Exchanges in Distribution: Retracing the Path of a Book Through a Centralized Medical Exchange - Connor, Jennifer (Mémoires du livre / Studies in Book Culture, 2018)
Expanding the concept of ownership to include distributorship allows consideration of a book route that diverges from circuits often associated with book culture studies. In particular, as this article outlines, organized publications exchanges—which temporarily own and distribute—present opportunities for understanding the spread of books from a different perspective. To demonstrate the research potential of exchanges, the article retraces the path of a single copy of a book over the twentieth century through a continental medical publications exchange, from its donation by the author to a county medical library outside Philadelphia, through its shipment to Toronto where it was housed in two medical libraries, and its brief return to Philadelphia in a personal collection in 2000. As the discussion suggests, this book, The Woman’s Medical College of Pennsylvania, its publication and its subsequent transnational peregrinations, spotlight the field of medicine with respect to contemporaneous trends in medical education, publishing, and library movements.